Resource curse or not: A question of appropriability - Anne D. Boschini; Jan Pettersson; Jesper Roine (Stockholm School of Economics, The Economic Research Institute (EFI), 2003)
This paper shows that whether natural resources are good or bad for a country's development depends crucially on the interaction between institutional setting and the type of resources that the country possesses. Some natural resources are for economical and technical reasons more likely to cause problems such as rent-seeking and conflicts than others (termed technically appropriable resources). This potential problem can, however, be countered by good institutional quality (rendering these resources less institutionally appropriable). In contrast to the traditional resource curse hypothesis we show that the impact of natural resources on economic growth is non-monotonic in institutional quality. Mineral rich countries are cursed only if they have low quality institutions, while the curse is reversed if institutions are good enough. Using new data we find that this is even more stark for countries rich in diamonds and precious metals.
Keywords: N50; O13; O40; O57; P16; 330; natural resources; appropriability; property rights; institutions; economic growth; development; Natürliche Ressourcen; Eigentumsrecht; Wirtschaftswachstum; Entwicklung; Institutionalismus